An identification algorithm for feedback active control - Anh, Nguyen Dong (Vietnam Journal of Mechanics, 2000)
The aim of the paper is to present a control law for feedback active controlled structures in which a control algorithm is proposed to identify the external excitation with a time delay. The time duration in which the external excitation acts on the structure is devised into subintervals. In each subinterval the external excitation is identified and is then selected with the opposite sign as the control force for the next subinterval. The realization of the identification control algorithm in the practical application mainly depends on the computing capacity of the involved computer. and requires an investigation with respect to its robustness and stabilization.